ISLAM DAN BUDAYA LOKAL (STUDI ATAS TRADISI KEISLAMAN MASYARAKAT JAWA) - Salman Faris (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2014)
AbstractThis paper tries to portray Islam in Java and matters which is relating tothe entry process of the Islamic culture into Javanese culture, the relationship between Islam and Javanese culture can be regarded as two sides of a coin that is not integral, which together determine the value of the currency. On the one hand, Islam comes and develops in Java influenced by tradition or Javanese culture. While on the other side, the Javanese culture increasingly enriched by Islamic repertoire. The relation between Islam and Javanese culture can be expressed in various aspects, including the interrelation and acculturation, in which both of them are the transformation of Islam into Javanese culture that has been adopted by the Java community before the advent of Islam. Interrelation and Islamic acculturation can take place easily in Java due to the open culture of Java to the presence of other cultures so that Islamic culture can go hand in hand with the culture that has been embraced by the population before the arrival of Islam in Java. The linkage between the traditions and Javanese culture is strongly associated with the teachings of Islam, especially in the fields of aqidah and syariah or Islamic law.Keywords: Interrelation, acculturation, transformation.